An overview of the existing problems faced by Pakistani women in agriculture: conclusion and recommendation. (6th July 2020) - Muhammad, Faheem; Hassan, Muhammad Azher; Mehmood, Tariq
Abstract : Purpose: The purpose of this paper is an attempt to cover available literature on natural resource management, which reflects the involvement of Pakistan communities living in different regions for sustainable management in agriculture, forestry and livestock sectors differentiated by women. In addition, it was also highlighted about the lack of access to productive resources for rural women farmers. The conclusion was drawn and key recommendation were suggested. Design/methodology/approach: It is authors real-life experiences or observations in a given field to support colleagues in a variety of ways including advising, establishing best practices and noting trends. Findings: It was concluded that there are no opportunities such as training of most advanced launched technologies for the sake of better crop production, dairy and fisheries sector sustainable development, as well as the availability of microfinance to support the women farmers in Pakistan rural areas to make them self-dependent. Originality/value: The opinions and key recommendations are genuine and useful, which should be adopted for the more bright future of women farmers, especially in Pakistan's rural area.